Base of tongue squamous cell carcinomas, outcome depending on treatment strategy and p16 status. A population-based study from the Swedish Head and Neck Cancer Register. (3rd April 2022) - Högmo, Anders; Holmberg, Erik; Haugen Cange, Hedda; Reizenstein, Johan; Wennerberg, Johan; Beran, Martin; Söderkvist, Karin; Hammerlid, Eva; Sjödin, Helena; Farnebo, Lovisa; Sandström, Karl; Hammarstedt-Nordenvall, Lalle; et al.
Abstract: Background: The base of tongue squamous cell carcinoma (BOTSCC) is mainly an HPV-related tumor. Radiotherapy (EBRT) ± concomitant chemotherapy (CT) is the backbone of the curatively intended treatment, with brachytherapy (BT) boost as an option. With four different treatment strategies in Sweden, a retrospective study based on the population-based Swedish Head and Neck Cancer Register (SweHNCR) was initiated. Material and methods: Data on tumors, treatment and outcomes in patients with BOTSCC treated between 2008 and 2014 were validated through medical records and updated as needed. Data on p16 status were updated or completed with immunohistochemical analysis of archived tumor material. Tumors were reclassified according to the UICC 8th edition. Results: Treatment was EBRT, EBRT + CT, EBRT + BT or EBRT + CT + BT in 151, 145, 82 and 167 patients respectively ( n = 545). A p16 analysis was available in 414 cases; 338 were p16+ and 76 p16−. 5-year overall survival (OS) was 68% (95% CI: 64–72%), with76% and 37% for p16+ patients and p16− patients, respectively. An increase in OS was found with the addition of CT to EBRT for patients with p16+ tumors, stages II–III, but for patients with tumor stage I, p16+ (UICC 8) none of the treatment strategies was superior to EBRT alone. Conclusion: In the present retrospective population-based study of BOTSCC brachytherapy was found to be of no beneficial value in curatively intended treatment. An increase in survival was found for EBRT + CT compared to EBRT alone in patients with advanced cases, stages II and III (UICC 8), but none of the regimes was significantly superior to EBRT as a single treatment modality for stage I (UICC 8), provided there was p16 positivity in the tumor. In the small group of patients with p16− tumors, a poorer prognosis was found, but the small sample size did not allow any comparisons between different treatment strategies.